Lung function, respiratory symptoms and venous thromboembolism risk: the Atherosclerosis Risk in Communities Study. (8th November 2016) - Kubota, Y.; London, S. J.; Cushman, M.; Chamberlain, A. M.; Rosamond, W. D.; Heckbert, S. R.; Zakai, N.; Folsom, A. R.
Abstract : Essentials The association of lung function with venous thromboembolism (VTE) is unclear. Chronic obstructive pulmonary disease (COPD) patterns were associated with a higher risk of VTE. Symptoms were also associated with a higher risk of VTE, but a restrictive pattern was not. COPD may increase the risk of VTE and respiratory symptoms may be a novel risk marker for VTE. Summary: Background: The evidence for the association between chronic obstructive pulmonary disease (COPD) and venous thromboembolism (VTE) is limited. There is no study investigating the association between restrictive lung disease (RLD) and respiratory symptoms with VTE. Objectives: To investigate prospectively the association of lung function and respiratory symptoms with VTE. Patients/Methods: In 1987–1989, we assessed lung function by using spirometry, and obtained information on respiratory symptoms (cough, phlegm, and dyspnea) in 14 654 participants aged 45–64 years, without a history of VTE or anticoagulant use, and followed them through 2011. Participants were classified into four mutually exclusive groups: 'COPD' (forced expiratory volume in 1 s [FEV1 ]/forced vital capacity [FVC] below the lower limit of normal [LLN]), 'RLD' (FEV1 /FVC ≥ LLN and FVC < LLN), 'respiratory symptoms with normal spirometic results' (without RLD or COPD), and 'normal' (without respiratory symptoms, RLD, or COPD). Results: We documented 639 VTEs (238 unprovoked and 401 provoked VTEs). After adjustment for VTE risk factors, VTE risk was increased for individuals with either respiratory symptoms with normal spirometric results (hazard ratio [HR] 1.40, 95% confidence interval [CI] 1.12–1.73) or COPD (HR 1.33, 95% CI 1.07–1.67) but not for those with RLD (HR 1.15, 95% CI 0.82–1.60). These elevated risks of VTE were derived from both unprovoked and provoked VTE. Moreover, FEV1 and FEV1 /FVC showed dose–response relationships with VTE. COPD was more strongly associated with pulmonary embolism than with deep vein thrombosis. Conclusions: Obstructive spirometric patterns were associated with an increased risk of VTE, suggesting that COPD may increase the risk of VTE. Respiratory symptoms may represent a novel risk marker for VTE.